Optimization of mix proportions and manufacturing conditions of fly ash-based geopolymer mortar by parameters design with dynamic characteristics. (October 2022) - Onoue, Kozo; Sagawa, Yasutaka; Atarashi, Daiki; Takayama, Yuji
Abstract: This study attempted to optimize a manufacturing system for fly ash-based geopolymer (FAGP) using parameters design with dynamic characteristics. In the system, the volume ratio of powder to alkaline solution was used as the input value, while the flow value after fifteen drops, flexural strength, and compressive strength of the mortar were used as output values. Fly ash production area, lot number, and testing institute were set as noise conditions. The mixing protocol, mass ratio of water glass to sodium hydroxide in an alkaline solution (SS/SH), sodium hydroxide concentration, mixing time, curing holding temperature, and cumulative temperature during curing were considered as design parameters. The SN ratio was calculated from optimization testing performed a total of 432 times, and the optimum level for each design parameter was found. By investigating the effects of individual design parameters on the reaction product of FAGP mortar through design of experiments method, it was found that the alkaline solution preparation method affects both fly ash reaction rate and the amount of C-A-S-H generated, and, compared with a combination in which the alkaline concentration of the alkaline solution is higher, a combination in which the alkaline concentration is lower exhibited a higher fly ash reaction rate with a lower amount of C-A-S-H generated. It was also found that, under optimum conditions for other design parameters, the fly ash reaction rate was high and the amount of C-A-S-H generated was low, which suggests that these are related to improvement of the reproducibility of FAGP mortar.